Verification of the method-of-moment codes using the method of manufactured solutions - Marchand, R.; Davidson, David (Institute of Electrical and Electronics Engineers, 2014)
The method of manufactured solutions (MMS) is introduced here for the verification of the method-of-moment (MoM) codes. The selection of appropriate manufactured solutions is investigated. The numerical integration of the electric field integral equation is discussed and the effect thereof on the utility of the MMS for the MoM is considered. General convergence rates of the MoM are discussed and the computation of the relevant norms is explained. Several examples are shown, highlighting the power of the MMS for different aspects of the code verification process. © 2014 IEEE.